An Analysis of Speech Acts in The Oliver Twist Script - Masfa Maiza; Ulya Himawati (English Education Department - Universitas Nasional Karangturi, 2022)
Language as a means of communication has an important role in delivering a message. Moreover, it is related to speech acts the speakers use. Each utterance has a different meaning to understand, and that is the job of the hearers and readers to interpret the meaning. Speech acts have three different distinct levels: locutionary (the actual words uttered), illocutionary (the force or intention behind the words), and perlocutionary (the effect of the illocution on the hearer). The researchers chose the “Oliver Twist” script as the data to analyse. Some of the scripts were taken and classified into the three levels of speech act: locutionary, illocutionary, and perlocutionary. This research aimed to describe the three distinct levels of speech acts that are shown in the “Oliver Twist” script and to examine how speech acts are used in the “Oliver Twist” script. The researchers used a descriptive analysis technique in which the data were taken from some scripts which contain three distinct levels of speech acts. The researchers then identified the utterances and classified how they performed what the speaker meant. The result shows that some utterances have three distinct levels of speech act, such as I want some more, You must be hungry, A polite boy, Can we start the game and Because he is a street child. Since speech acts are essential to indicate what a speaker means, English learners should enrich themselves by understanding the function of speech acts and their distinct levels.